Open access publishing: implications for libraries. - Wood EH (Journal of Electronic Resources in Medical Libraries, 2005)
The recent movement towards 'open access publishing' has developed very quickly. It began with publishers such as Public Library of Science and BioMed Central, persuading researchers to publish in their subscription-free or very low-cost journals. Commercial publishers then joined in, suggesting that authors pay a fee to have articles available free of charge on the Web. Most recently, government and professional organizations are recommending that research results be published this way. Implications for libraries include the impact on subscription costs, institutional subsidizing of authors' fees, and libraries' negotiations with administrators.